A survey of Methylobacterium species and strains reveals widespread production and varying profiles of cytokinin phytohormones - Palberg, Daniel; Kisiała, Anna; Jorge, Gabriel Lemes [UNESP]; Emery, R. J. Neil (Springer Nature, 2022)
Background: Symbiotic Methylobacterium strains comprise a significant part of plant microbiomes. Their presence enhances plant productivity and stress resistance, prompting classification of these strains as plant growth-promoting bacteria (PGPB). Methylobacteria can synthesize unusually high levels of plant hormones, called cytokinins (CKs), including the most active form, trans-Zeatin (tZ). Results: This study provides a comprehensive inventory of 46 representatives of Methylobacterium genus with respect to phytohormone production in vitro, including 16 CK forms, abscisic acid (ABA) and indole-3-acetic acid (IAA). High performance-liquid chromatography—tandem mass spectrometry (HPLC–MS/MS) analyses revealed varying abilities of Methylobacterium strains to secrete phytohormones that ranged from 5.09 to 191.47 pmol mL−1 for total CKs, and 0.46 to 82.16 pmol mL−1 for tZ. Results indicate that reduced methanol availability, the sole carbon source for bacteria in the medium, stimulates CK secretion by Methylobacterium. Additionally, select strains were able to transform L-tryptophan into IAA while no ABA production was detected. Conclusions: To better understand features of CKs in plants, this study uncovers CK profiles of Methylobacterium that are instrumental in microbe selection for effective biofertilizer formulations.
Keywords: 2-methylthio-Zeatin; HPLC–MS/MS; Methanol; Plant growth promoting bacteria; trans-Zeatin